The Global Financial Crisis and the Export-Led Economic Growth in China. Issue 3 (4th May 2019) - Liu, Ming-Hua; Margaritis, Dimitris; Zhang, Yang
Abstract : The growing trade conflict with the United States has heightened concerns on the progress of China's economic rebalancing and restructuring from export-led growth strategy to one propelled by domestic consumption. This article examines the role of exports in China's economic growth in both the short run and the long run. Using an ARDL model and quarterly time series data from 1994 and 2018, we find evidence indicating heightened importance of exports in China's GDP growth after the Global Financial Crisis, and our results suggest that the transition from an export-led growth strategy is proceeding far less smoothly than hoped.